2005
DOI: 10.1681/asn.2004110932
|View full text |Cite
|
Sign up to set email alerts
|

Altered Morphologic Properties of Large Arteries in Children with Chronic Renal Failure and after Renal Transplantation

Abstract: Increased intima-media thickness of the carotid arteries (cIMT) has been found in young adults with childhood-onset chronic kidney disease (CKD). The disease stage at which these patients first develop abnormalities of arterial texture is unknown. The objective of this study was to determine the onset and character of arterial changes in children aged 10 to 20 yr with different stages of CKD and to identify risk factors for early arteriopathy. High-resolution ultrasonography was conducted of common cIMT and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
6
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(224 citation statements)
references
References 39 publications
15
190
6
6
Order By: Relevance
“…Other investigators have similarly demonstrated that children with varying degrees of kidney dysfunction have higher cIMT than the general population, with dialysis patients having the most extremely elevated measurements (17,18). What makes our results particularly striking is that this finding still holds among children without extreme kidney dysfunction or ESRD compared with normative data obtained in a more racially diverse, representative group of healthy controls.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Other investigators have similarly demonstrated that children with varying degrees of kidney dysfunction have higher cIMT than the general population, with dialysis patients having the most extremely elevated measurements (17,18). What makes our results particularly striking is that this finding still holds among children without extreme kidney dysfunction or ESRD compared with normative data obtained in a more racially diverse, representative group of healthy controls.…”
Section: Discussionsupporting
confidence: 61%
“…However, there is a growing body of literature demonstrating increased cIMT in children with CKD (17,18). In addition, among children, increased cIMT is associated with hypertension, obesity, diabetes, and metabolic syndrome and is affected by interventions to decrease cardiovascular risk such as statin therapy, diet, and exercise (15).…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the USRDS database, Parekh et al reported that 311 of the 1,380 (22.5%) deaths in patients aged 0-30 years who had undergone dialysis between 1990 and 1996 were from a cardiac cause [60]. Similarly, ANZDATA [3], the Dutch cohort [4], and German [11] and Polish [61] single-centre studies reported cardiovascular disease as the single most common cause of death in their CKD patients. Chavers et al presented the largest study on cardiovascular morbidity in children on dialysis from the Medicare database [62].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Studies of children with stages 2-4 CKD and on dialysis have shown that increased intima-media thickness of the carotid artery [61,67,103] (a measure of structural changes in the vessel wall), increased pulse wave velocity [67,104,105] (a measure of stiffness or loss of compliance of the vessel) and presence of coronary and valvular calcification on CT scan [67,82,106] are present as early as the first decade of life. Secondary hyperparathyroidism, with the associated increase in calcium and phosphate levels [64], and renal bone disease [107], as well as its treatment with calcium-based phosphate binders [61,108] and vitamin D [61,67,103], have been implicated as major cardiovascular risk factors.…”
Section: Vascular Calcificationmentioning
confidence: 99%
See 1 more Smart Citation